Muonium diffusion in solid CO₂ - Eshchenko, D.G.; Storchak, V.G.; Brewer, J.H.; Cottrell, S.P.; Cox, S.F.J.; Karlsson, E.; Waeppling, R. (Физика низких температур, 2001)
The quantum diffusion of interstitial muonium atoms in solid CO₂ is studied in the temperature range from 5 to 200 K using the technique of muonium spin rotation and relaxation. Muonium exhibits coherent bandlike dynamics between 140 and 160 K. At low temperature Mu undergoes strong localization.